Capacitive imaging of impact damage in composite material. (15th March 2017) - Morozov, Maxim; Jackson, William; Pierce, S.G.
Abstract: This work presents capacitive non-destructive imaging of impact damage in woven fibre CFRP using a coplanar capacitive sensor. Novelty of the approach consists in that spectral characteristics of the capacitive sensor response to CFRP properties are firstly used to establish excitation frequencies for optimum imaging of delamination. For the tested samples optimum excitation frequencies were found to be above 200 MHz. Clear capacitive images of delaminations were obtained on each sample. Ultrasonic (UT) C-scans of delaminations due to impacts were acquired using phased array technique to confirm presence and extent of the delaminations. Capacitive imaging technique can be used as complementary to UT for imaging shallow defects in composite materials at depths where UT has insufficient time domain resolution.